Based on the network degeneration hypothesis: Separating individual patients with different neurodegenerative syndromes in a preliminary hybrid PET/MR study - Tahmasian, Masoud; Shao, Junming; Meng, Chun; Grimmer, Timo; Diehl-Schmid, Janine; Yousefi, Behrooz H.; Foerster, Stefan; Riedl, Valentin; Drzezga, Alexander; Sorg, Christian (Journal of Nuclear Medicine, 2016)
The network degeneration hypothesis (NDH) of neurodegenerative syndromes suggests that pathologic brain changes distribute primarily along distinct brain networks, which are characteristic for different syndromes. Brain changes of neurodegenerative syndromes can be characterized in vivo by different imaging modalities. Our aim was to test the hypothesis whether multimodal imaging based on the NDH separates individual patients with different neurodegenerative syndromes. Methods: Twenty patients with Alzheimer disease (AD) and 20 patients with frontotemporal lobar degeneration (behavioral variant frontotemporal dementia [bvFTD, n 5 11], semantic dementia [SD, n 5 4], or progressive nonfluent aphasia [PNFA, n 5 5]) underwent simultaneous MRI and 18F-FDG PET in a hybrid PET/MR scanner. The 3 outcomemeasureswere voxelwise values of degree centrality as a surrogate for regional functional connectivity, glucose metabolism as a surrogate for regional metabolism, and volumetric-based morphometry as a surrogate for regional gray matter volume. Outcome measures were derived from predefined core regions of 4 intrinsic networks based on theNDH,which have been demonstrated to be characteristic for AD, bvFTD, SD, and PNFA, respectively. Subsequently, we applied support vector machine to classify individual patients via combined imaging measures, and results were evaluated by leave-one-out cross-validation. Results: On the basis of multimodal voxelwise regional patterns, classification accuracies for separating patients with different neurodegenerative syndromes were 77.5% for AD versus others, 82.5% for bvFTD versus others, 97.5% for SD versus others, and 87.5% for PNFA versus others. Multimodal classification results were significantly superior to unimodal approaches. Conclusion: Our finding provides initial evidence that the combination of regional metabolism, functional connectivity, and gray matter volume, which were derived from disease characteristic networks, separates individual patients with different neurodegenerative syndromes. Preliminary results suggest that employing multimodal imaging guided by the NDH may generate promising biomarkers of neurodegenerative syndromes.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Alzheimer's disease; Frontotemporal lobar degeneration; Hybrid PET/MR; Network degeneration hypothesis; Neurodegenerative syndromes